The Existence of Equilibrium in a Financial Market with General Personal and Corporate Tax Structures - Xing Jin; Frank Milne (Queen's University, Department of Economics, 1996)
This article concerns the existence of equilibrium in a two-period model with general personal and corporate tax structures. We show that an equilibrium exists if there is a price system under which no consumer or firm has an arbitrage opportunity. The model can be modified to handle non convex tax structures and capital gains.
Keywords: G1; H2; D5; 330; general equilibrium; financial markets; taxation; general equilibrium; financial markets; taxation